Algebra 2

posted by .

Find f(x), if f(2b-1)=6b+2

• Algebra 2 -

let 2b - 1= x
2b = x+1
b = (x+1)/2

then for
f(2b-1) = 6b = 2
f(x) = 6(x+1)/2 + 2
=3(x+1) + 2
= 3x + 5

f(x) = 3x + 5

check by replacing x with 2b-1
f(2b-1) = 3(2b-1) +5 = 6b -3+5
= 6b + 2 , as given

Similar Questions

1. Algebra

Hi, I need to use algebra to find the x-and y-intercepts for the parabola −3x^2 +6x +9 = 0 Any ideas or help appreciated
2. Algebra

Hi, Any help on this would be very much appreciated. The graph y=3x^2+6x+9 is a parabola, I need to use algebra to find the equation of the axis of symmetry, I then need to use this information to find the coordinates of the vertex. …
3. Algebra

I need some help with algebra as I'm confused as to how to solve them. Find the common difference d and the value of a1 using the information given. 1. a6= 5/4, a8= 9/4 Evaluate each sum. 2. E like symbol that has a 29 on the top. …

Find the number of terms in each sequence. 1. 2,-6, 18,-54,,,,,-4374 Find the common ratio r and the value of a1 using the information given. (assume r >0) 2.a3=324, a7=64 Find the indicated sum. 3. a1=2, r=-3; find s8 4. E like …

Find the number of terms in each sequence. 1. 2,-6, 18,-54,,,,,-4374 Find the common ratio r and the value of a1 using the information given. (assume r >0) 2.a3=324, a7=64 Find the indicated sum. 3. a1=2, r=-3; find s8 4. E like …

Find the number of terms in each sequence. 1. 2,-6, 18,-54,,,,,-4374 Find the common ratio r and the value of a1 using the information given. (assume r >0) 2.a3=324, a7=64 Find the indicated sum. 3. a1=2, r=-3; find s8 4. E like …
7. algebra

Find the number of terms in each sequence. 1. 2,-6, 18,-54,,,,,-4374 Find the common ratio r and the value of a1 using the information given. (assume r >0) 2.a3=324, a7=64 Find the indicated sum. 3. a1=2, r=-3; find s8 4. E like …
8. Algebra

I can find the finite differences, but how do I find the number of birds in July?
9. Algebra 2

Did I answer these correctly? 1.f(x) = 2x + 3 g(x)= 2x^2 + 2x Find f(g(x) ) 2(2x^2+2x)+3 =4x(x+1)+3 = 4x^2+4x+3 2. f(x) = 5x + 3 g(x) = 2x^2-2x + 2 Find (fg(x) ) (5x+3)(2x^2-2x+2) 2(5x+3)(x^2-x+1) 10x^3-4x^2+4x+6 3.f(x)=3x g(x)= -2x^2
10. Algebra

y^2-x-4=0 a)find all x and y intercepts of the graph implied by this equation. (use an appropriate equation). b) test the graph for symmetry using algebra. (explain reasoning through algebra)

More Similar Questions